Key factor for low anisotropy and high irreversibility field in (Cu, C)Ba2Ca3Cu4O11+δ. (December 2022) - He, Chengping; Ming, Xue; Lin, Renju; Fan, Xinwei; Song, Dongsheng; Ge, Binghui; Wen, Hai-Hu
Abstract: In cuprate superconductors, the Hg-, Tl- and Bi-based systems with multilayers of CuO2 planes within one unit cell usually have critical temperatures higher than 100 K. However, the applications of these materials under high magnetic fields in liquid nitrogen temperature region are strongly limited by the very high anisotropy and strong vortex motion. The observation of an unprecedented high irreversibility field and low anisotropy in (Cu, C)Ba2 Ca3 Cu4 O11+ δ with T c  = 116 K was an exception, and the reason remains elusive. Here, we report the investigations on (Cu, C)Ba2 Ca3 Cu4 O11+ δ single crystals. The angle-dependent resistivity under different temperatures and magnetic fields reveals clear evidence of lower anisotropy and higher irreversibility fields. The high resolution scanning transmission electron microscopy allows to clearly visualize that CuO chains and CO chains are formed alternatively at the places where the heavy metal oxides would locate. First-principle calculations confirm that the newly formed CuO chains in the charge reservoir blocks significantly enhance the c -axis coherent electronic conduction, lower the anisotropy and strengthen the irreversibility field. This discovery may be extended in a general sense to other layered cuprates and stimulate high power applications of cuprate superconductors in liquid nitrogen temperature region. Graphical abstract: Image 1 Highlights: The low anisotropy and high irreversibility fields are confirmed in (Cu, C)-1234 single crystals. For the first time, we visualize the alternatively arranged chains of CuO and carbon-oxygen based octahedrons in the charge reservoir block. The newly formed CuO chains in the reservoir block significantly enhance the c-axis coherent electronic conduction, lower down the anisotropy and strengthen the irreversibility field.